THE DEVELOPMENT OF A WEB BASED DATABASE APPLICATIONS OF PROCUREMENT, INVENTORY, AND SALES AT PT. INTERJAYA SURYA MEGAH - Choirul Huda; Chendra Hudyanto; Sisillia Sisillia; Revin Kencana Persada (CommIT (Communication and Information Technology) Journal, 2011)
The objective of this research is to develop a web based database application for the procurement, inventory and sales at PT. Interjaya Surya Megah. The current system at PT. Interjaya Surya Megah is running manually, so the company has difficulty in carrying out its activities. The methodology, that is used in this research, includes interviews, observation, literature review, conceptual database design, logical database design and physical database design. The results are the establishment of a web-based database application at PT. Interjaya Surya Megah. The conclusion is the company can be easier to run the day-to-day activities because data processing becomes faster and more accurate, faster report generation and more accurate, more secure data storage.Keywords: database; application; procurement; inventory; sales